Tendencies of the volleyball serving skill with respect to the serve type across genders - Kitsiou, A.; Sotiropoulos, K.; Drikos, S.; Barzouka, K.; Malousaris, G. (Journal of Physical Education and Sport, 2020)
The purpose of this study was to investigate the areas from which the serves performed by elite volleyball players were carried out, the zones into where they were directed and their performance in respect to the serve type used per gender. A three-member group of coaches assessed the serve actions of male (M) and female (F) elite players from 20 volleyball games (M=10, F=10) of National Teams competing in the final phase of the World League 2018. The analyzed variables comprised the serve type, the area from which the serve was carried out (SA), the serve direction and the serve performance which was assessed based on a 5-level tactical rating scale (Eom & Schutz, 1992). Results showed thatmen mainly preferred the power jump serve (PJS) while women the float jump serve (FJS). Both genders irrespective of the serve type used chose mainly the SA behind zone 1 (SA1) for the execution of their serves. However, men used the SA behind zone 5 (SA5) for the execution of their FJS more frequently compared to women who preferred the SA1 for the execution of both the PJS and the FJS as well. Women directed the PJS into the central part of the court and the FJS into zone 5 more frequently than men. On the other hand, men directed the PJS into zone 5, the FJS into zones 7 and 8 and made more mistakes than women. Moreover, they presented a higher proportion of PJS which directed into zone 5 and evaluated as very good compared to women. In addition, irrespective of the serve type used men made more errors than women who created more often ideal conditions for the opponent setter to organize the game.